Evidence for a Numerosity Category that is Based on Abstract Qualities of “Few” vs. “Many” in the Bottlenose Dolphin (Tursiops truncatus) - Yaman, Sevgi; Kilian, Annette; von Fersen, Lorenzo; Güntürkün, Onur (Frontiers in Psychology, 2012)
A previous study (Kilian et al., 2003) had demonstrated that bottlenose dolphins can discriminate visual stimuli differing in numerosity. The aim of the present study was twofold: First, we sought to determine if dolphins are able to use a numerical category based on ‘few’ versus ‘many’ when discriminating stimuli according to the number of their constituent patterns. Second, we aimed to extend the previously demonstrated range of numbers, thereby testing the limits of the numerical abilities of bottlenose dolphins. To this end, one adult bottlenose dolphin learned to discriminate between two simultaneously presented stimuli which varied in the number of elements they contained. After initial training, several confounding parameters were excluded to render it likely that discrimination performance indeed depended on numerosity. Subsequently, the animal was tested with new stimuli of intermediate as well as higher numbers of elements. Once discrimination had been achieved, a reversal-training on a subset of stimuli was initiated. Afterwards, the subject generalized the reversal successful to new and unreinforced stimuli. Our results reveal two main findings: Firstly, our data strongly suggest a magnitude and a distance effect. Thus, coding of numerical information in dolphins might follow logarithmic scaling as postulated by the Weber-Fechner law. Secondly, after learning a reversal of contingencies, the dolphin generalized the reversal successful to new and unreinforced stimuli. Thus, within the limits of a study that was conducted with a single individual, our results suggest that dolphins are able to learn and use a numerical category that is based on abstract qualities of ‘few’ versus ‘many’.